(3GdhGajI aj TQM GdcGajI GdTGajIs - (3eMeO Hf YHO Gddg, GHf eGdc GdWGFj GdLqjGfj, CHh YHO Gddg, LeGd GdOjf,J (B672 (3g` s
(3ChdgG (B:s
(3Chdg HGH CSeGA GdCaYGd hGdCUhGJ (B: (3fGFH aYd ZjQ eYehd hdG aUdg GSe GdaYd hGdeLOi CaYdG s
(3BNQgG (B:s
(3hbO LYdJ fXe gPG GdHGH ecedG CHhGH PG GdcJGH aGdMeO ddg Ydi Jcejdg ejSQkG eGQje ef JMUjdg s
(3cJHJ GdYfGhjjf HGdMeQIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B223 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B130s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdfMhs